EDI-based deinterlacing using edge patterns - Min Byun; Min Kyu Park; Moon Gi Kang (IEEE International Conference on Image Processing 2005, 2005)
In this paper, a new EDI-based deinterlacing algorithm is proposed. Generally, EDI algorithms perform visually better than any other intrafield deinterlacing algorithm. However, they produce unpleasant results due to their failure in estimating edge direction. To estimate the edge direction precisely, not only simple difference between adjacent two lines but also edge patterns are used. Here, we analyze properties of edge patterns and model them as weight functions. The weight functions help the proposed method to estimate the edge direction precisely.